Working Smarter Together: Models of Interprofessional Collaboration in Outpatient Palliative Care Clinics (SA309) - Fukui, Natsu; Fisher, Lorin; Hensiek, Sarah; Pool, Katie; Terauchi, Stephanie (Journal of pain and symptom management, 2022)
Outcomes 1. Distinguish 3 models of interprofessional collaboration in outpatient palliative care 2. Describe approaches for each interprofessional team member to practice at the top of their licenses in outpatient palliative care 3. Discuss strategies to maximize interprofessional collaboration in outpatient palliative care using a case-based approach Outpatient palliative care clinics are growing in number, size, and scope of practice at many institutions. With this growth, some outpatient practices are facing challenges with staffing shortages and limited appointments, which can lead to overwhelmed staff and delays in patient scheduling. A review article examining diverse models of outpatient palliative care practices concluded that interprofessional specialist palliative care in stand-alone clinics provides the greatest benefits and should be the gold standard approach. However, relative to inpatient palliative care, models of interprofessional collaboration in outpatient palliative care are still a work in progress. Unfortunately, there remains a paucity of literature to guide how to maximize the expertise of team members with various professional backgrounds in the clinic setting. How can outpatient palliative care teams navigate these challenges and maximize the unique strengths of diverse disciplines so that each team member can practice at the top of their licenses? In this session, an interprofessional team of clinicians from across the United States will describe 3 different outpatient palliative care practice models. We will highlight unique roles interprofessional team members—specifically clinical pharmacist, registered nurse coordinator, and social worker—play in our clinics. We will share our experiences developing strategies to maximize team productivity by promoting the skill sets and strengths of different disciplines while also maintaining team cohesion. Using a sample case, we will provide an opportunity for attendees to participate in a small group discussion and exchange ideas on how to optimize interprofessional collaboration. We hope the knowledge gained by participating in this session will spark creative ideas among the attendees and allow for the development of actionable strategies to improve interprofessional collaboration in the palliative care clinics at their home institutions.